Tertiary lymphoid structures marker CXCL13 is associated with better survival for patients with advanced-stage bladder cancer treated with immunotherapy. (May 2021) - Groeneveld, Clarice S.; Fontugne, Jacqueline; Cabel, Luc; Bernard-Pierrot, Isabelle; Radvanyi, François; Allory, Yves; de Reyniès, Aurélien
Abstract: Introduction: Immune checkpoint inhibitors (ICIs) have proved to be an effective treatment for up to 40% of muscle-invasive bladder cancer (MIBC), but there is still a need for better performing biomarkers allowing to improve prediction of response to ICI. Response to immunotherapy in soft-tissue sarcoma, melanoma and renal cell carcinoma have been recently linked to the presence of tertiary lymphoid structures (TLS) in the tumour. TLS are organised aggregates of T, B and dendritic cells, participating in adaptive antitumor immune response. The chemokine CXCL13 is involved in the formation of TLS, and is reported as a reliable transcriptomic marker of TLS. Objectives: In this study, we sought to assess whether CXCL13 transcript expression can be a prognostic biomarker for ICI-treated MIBC patients and also investigated whether it can serve a biomarker of TLS in MIBC. Methods: We analysed transcriptomic data from three publicly available MIBC cohorts and evaluated pathological slides from the TCGA-BLCA cohort for TLS presence and stage of maturation. Results: We showed that CXCL13 was independently associated with both prolonged survival (HR = 0.8, 95% CI [0.68–0.94]) and objective response ( p < 0.0001) in patients treated with ICI, at the difference of others immunological signatures. However, it was not a predictor for non–ICI-treated MIBC, suggesting a predictive effect of ICI efficacy. Finally, we validated that CXCL13 expression was correlated with tumour TLS in TCGA data set ( p < 0.001), and can serve as a marker of TLS in bladder cancer. Conclusion: These results support that CXCL13 expression, as a surrogate for tumour TLS, is a relevant candidate predictive biomarker of response to ICI for patients with advanced-stage bladder cancer. Graphical abstract: Image 1 Highlights: CXCL13 expression predicts survival for advanced-stage MIBC treated with ICI. CXCL13 expression correlates with the presence of TLS in TCGA tumours. Ba/Sq and stroma-rich subtypes have higher CXCL13 expression and harbour more TLS. We suggest CXCL13 as a predictive biomarker for ICI response in bladder cancer.